Brand image, customer satisfaction, and loyalty in Mineral Water industry: a mediation analysis - Yafi, Muhammad Agra; Wardi, Yunia (Universitas Negeri Padang, 2025)
The purpose of this research is to investigate the impact of brand image of Aqua bottled water products and other bottled water brands on customer loyalty, with customer satisfaction acting as a mediating factor. The intense competition within Indonesia's bottled water industry, coupled with the shifting consumer perceptions driven by external socio-political issues, highlights the need to understand the factors that drive customer loyalty. This research employs a quantitative approach with a causal research design, involving 150 respondents from Padang City, selected By employing purposive sampling. Data were collected using a structured online questionnaire (Google Forms) and analyzed with Partial Least Squares (PLS) using SmartPLS software. The findings indicate that Aqua’s brand image Positively and significantly impacts customer loyalty, both in a direct manner and through the mediation of customer satisfaction. as a mediator. Conversely, the brand image of competing bottled water brands negatively affects customer loyalty. Furthermore, customer satisfaction plays a crucial mediating role, strengthening The connection between brand image and customer loyalty. These findings emphasize the importance for companies to maintain a strong brand image and continuously improve customer satisfaction to enhance consumer loyalty in an increasingly competitive market.